The Role of Job Rotation and Organizational Communication on Job Satisfaction and Employee Performance: Evidence from Jakarta’s Banking Industry - Sitta Kusuma (Transpublika Publisher, 2025)
Employee performance is a key factor that determines organizational success because it directly affects productivity and competitiveness. In the banking sector, intense competition demands effective human resource management through strategies such as job rotation, organizational communication, and job satisfaction improvement. This paper aimed to identify and analyze the determinants that bear upon employee performance while simultaneously offering prescriptive insights for organizational leadership. The focal constructs examined as antecedents of performance encompass job rotation, organizational communication, and job satisfaction. Adopting a quantitative orientation, the investigation surveyed personnel within a banking institution located in the Special Capital Region of Jakarta, comprising 240 respondents deemed suitable for inclusion. Methodologically, the study employed descriptive exploration, assessments of construct validity and reliability, alongside Structural Equation Modeling (SEM) as the principal analytical apparatus. Empirical findings affirm that job rotation exerts a favorable and statistically significant influence on job satisfaction, organizational communication likewise yields a constructive and significant impact on job satisfaction, and both job rotation and organizational communication independently manifest positive and significant effects on employee performance. Further, job satisfaction itself emerges as a salient and significant driver of performance outcomes. These findings highlight the importance of effective job rotation and organizational communication in improving job satisfaction, which in turn strengthens employee performance in the banking sector.